Ragam Penelitian Kualitatif Berbasis Kepustakaan Pada Studi Agama dan Keberagamaan dalam Islam - Saefullah, Agus Susilo (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to describe the diversity of literature-based qualitative research applied in the study of religion and religiosity in Islam. Through descriptive qualitative research methods with library data collection, this research explores a variety of research that can be used in research on religion and diversity in Islam. The results show various research from various angles that can be applied in literature-based studies of religion and diversity in Islam. First, in terms of the type of research, namely the study of revelation texts, the study of figures' thoughts, textbook analysis, and historical studies. Second, in terms of research approaches, namely theological, anthropological, sociological, historical, interpretive, biographical research, hermeneutics, and artifact studies. The three research methods are descriptive, theoretical, comparative (muqaranah), historical and critical. Fourth, in terms of research data analysis, content analysis, discourse analysis, historical analysis, critical analysis, textual analysis, narrative analysis, and narrative analysis, thematic analysis, descriptive analysis, intertextual. The implication of this research is to enrich the insight of academics and researchers in choosing appropriate research methods for studying Islamic religion and diversity and encouraging the use of more varied, combinative, and in-depth qualitative research. The suggestions include integrating more interdisciplinary approaches, methods, and analysis in studying Islamic religion and diversity to produce more comprehensive findings relevant to current developments. In addition, researchers are expected to be able to develop analytical and critical skills in evaluating literature, which will help enrich academic discourse in this field.